Pengaruh Pemberian Kompres Panas Dan Kompres Dingin Terhadap Penurunan Nyeri Pada Low Back Pain Myogenic - Aminudun, Muhammad Faqih, Wahyuni, SSt.FT.M.Kes, Dwi Kurniawati, SSt.FT, Arif Pristianto, SSt.FT.,M.Fis (2016)
Low Back Pain Myogenic is lower back pain caused by disorders or musculoskeletal disorders without any neurological impairment. LBP Myogenic caused by mechanical factors, shock, poor activity, obesity weak physical condition, the error at the time of the bed and stood, and lifting weights too heavy. Modalities that can be used to treat pain myogenic LBP is hot and cold pack, The purpose of this study to determine effect of hot and cold pack to decrease of pain in LBP myogenic. This research used quasi experimental design with pre-test and post-test control group design. The research was conducted in Kembang village Juwiring District of Klaten regency, study subjects were farm laborers who meet the criteria that have been defined and obtained 22 votes. Decreased in pain was measured with oswestry disability index (ODI) before and after training, data processing and data analysis using SPSS. The effect of using the Wilcoxon test and the test of differences using Mann-Whitney Test. Wilcoxon test results showed that have effect of hot packs and cold compresses to the decrease Myogenic LBP. Results of Mann-Whitney test showed that there were significant differences between of hot and cold compress to the decrease Myogenic LBP. With the value of p = 0,041 so p <a (0.05). Keywords : hot pack, cold pack, oswestry disability index (ODI).